Comparison of intravenous dexmedetomidine versus ketamine–dexmedetomidine combination on spinal block characteristics in patients undergoing lower limb orthopaedic surgery – A randomised clinical trial - Annapureddy Sai Krishna; Jyotsna Agarwal; Samiksha Khanuja; Sandeep Kumar; Adam Khan; Khairat Mohammad Butt (Indian Journal of Anaesthesia)
Background and Aims: One major limitation of the spinal block remains the inability to extend the duration of the block intraoperatively unless planned before with spinal or epidural catheters and/or intrathecal additives. This study was designed to compare the effects of intravenous dexmedetomidine versus low-dose ketamine–dexmedetomidine combination infusion on spinal anaesthesia in lower limb orthopaedic surgeries. Methods: This randomised study was conducted in 60 patients scheduled for unilateral lower limb surgeries under spinal anaesthesia. Patients were randomised into Group D (n = 30) (0.5 µg/kg of intravenous (IV) dexmedetomidine bolus followed by maintenance infusion at 0.5 µg/kg/h) and Group LKD (n = 30) (IV bolus of 0.5 µg/kg of dexmedetomidine and 0.2 mg/kg of ketamine, followed by maintenance infusions of dexmedetomidine and ketamine at 0.5 µg/kg/h and 0.2 mg/kg/h, respectively). Ramsay Sedation Scale score of 3–4 was maintained. The t-test or the Wilcoxon–Mann–Whitney U test was used to compare the parameters between groups. Results: The mean sacral segment 1 (S1) regression time was 390.3 [standard deviation (SD):84.38] [95% confidence interval (CI): 360.13, 420.53] versus 393.23 (SD: 93.01) (95% CI: 363.04, 423.43) min in Group D versus Group LKD respectively ((P = 0.701). The number of episodes of hypotension was significantly higher in Group D (19 patients) compared to Group LKD (nine patients) (P = 0.001). Pre- and postoperative stress markers (24 h) and the incidence of postoperative nausea and shivering were comparable between the two groups (P > 0.05). Tramadol requirement in the postoperative period was significantly less in Group LKD compared to Group D (P = 0.003). Conclusion: The duration of S1 regression was similar between group dexmedetomidine (Group D) and group low-dose ketamine and dexmedetomidine (Group LKD).